PENINGKATAN KAPASITAS UMKM MELALUI PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DI KELURAHAN PANGKAJENE, KECAMATAN MARITENGNGAE, KABUPATEN SIDENRENG RAPPANG - Ayu, Ari; Sumartan, Sumartan; Putri P, Andi Sri Kumala; Suriadi, Suriadi; Nurwafiyyah, Auliyah; Basri, Jumriah; Nirmasari, Dian; Asrini, Asrini; Putri D, A. Kartini Sari; Heady S, Muhammad G. Try (Universitas Mataram, 2025)
Awareness of the importance of financial literacy among MSME actors demands appropriate interventions in the form of comprehensive education and continuous mentoring. This community service program aimed to enhance the financial management capacity of Micro, Small, and Medium Enterprises (MSMEs) through training and mentoring on basic financial reporting. The program was implemented in Pangkajene Urban Village, Sidenreng Rappang Regency, involving 15 MSME actors from the food, handicraft, and service sectors. The methods included problem identification, basic accounting training, financial recording practice, and intensive individual and group mentoring. The results showed a significant improvement in participants’ understanding of basic accounting concepts and their ability to prepare simple income statements and daily cash records. Furthermore, participants responded positively and demonstrated a strong commitment to implementing consistent financial recordkeeping in their businesses. However, challenges such as consistency in recording and difficulty understanding accounting terms were still present. This activity demonstrates that a practical, mentoring-based approach is effective in strengthening the financial capabilities of MSME actors